Application of Non-Targeted Analysis Methods in Adulteration Detection and Prediction of Process Parameters of Vinegars - Çavdaroğlu, Çağrı; Çavdaroğlu, Çağrı; Özen, Fatma Banu (01. Izmir Institute of Technology, 2023)
Vinegar plays a multifaceted role in human diet, encompassing nutritive, functional, and taste-enhancing aspects. Quality of vinegar is influenced by quality of raw materials and production methods employed. Spectroscopic techniques offer distinct advantages in terms of speed and environmental friendliness, making them valuable tools for monitoring and controlling food production processes. This study has two major parts. In the first part, traditional and commercial grape vinegar production were monitored using both chemical parameters (total acidity, pH, brix, ethanol etc.) and mid-infrared (mid-IR) and UV-visible (UV-vis) profiles. These measured chemical parameters were predicted from spectral profiles in combination with multivariate statistical analysis techniques. In the second part, mid-IR, UV-vis and fluorescence spectroscopic techniques were used in determination of adulteration of both grape and apple vinegar with acetic acid and spirit vinegar at various ratios. Capability of spectroscopic methods combined with chemometrics were tested for prediction of various chemical parameters of vinegar as well as detection of adulteration of vinegar with different adulterants. Those techniques have proven to be effective in estimating the overall quantities of sugars, phenolics, flavonoids, and organic acids. Utilizing chemometric models with UV–vis and mid-IR data yielded high rates of correct classification, sensitivity, and specificity, particularly for adulteration levels exceeding 5% in vinegar. The performance of mid-IR spectroscopy demonstrated success in detecting the presence of spirit vinegar and acetic acid in apple vinegar. Overall, with this thesis, the usefulness of spectroscopic methods was highlighted by emphasizing the importance of chemometric tools for the parameter prediction and detection of vinegar adulteration.

Sirke, insan beslenmesinde besleyici, işlevsel ve tat arttırıcı bir rol oynar. Sirke kalitesi, kullanılan hammaddelerin kalitesinden ve üretim yöntemlerinden etkilenir. Spektroskopik teknikler hız ve çevre dostu olma açısından belirgin avantajlar sunarak onları gıda üretim süreçlerinin izlenmesi ve kontrolünde değerli araçlar haline getirmektedir. Bu çalışma iki ana bölümden oluşmaktadır. İlk bölümde, geleneksel ve ticari üzüm sirkesi üretimi hem kimyasal parametreler (toplam asitlik, pH, briks, etanol vb.) orta kızılötesi (mid-IR) ve UV-görünür (UV-vis) profilleri kullanılarak izlenmiştir. Ölçülen kimyasal parametreler, çok değişkenli istatistiksel analiz teknikleriyle spektral profillerden tahmin edilmiştir. İkinci bölümde üzüm ve elma sirkesinin asetik asit ve beyaz sirke ile çeşitli oranlarda tağşişinin belirlenmesinde mid-IR, UV-vis ve floresans spektroskopik teknikleri kullanılmıştır. Kemometri ile birleştirilmiş spektroskopik yöntemlerin başarısı, sirkenin çeşitli kimyasal parametrelerinin belirlenmesinin yanı sıra sirkenin farklı tağşiş maddeleri ile hilesinin tespiti için test edilmiştir. Bu tekniklerin şeker, fenolik madde, flavonoid ve organik asitlerin genel konsantrasyonunu tahmin etmede etkili olduğu kanıtlanmıştır. Ancak toplam şeker, fenolik madde veya organik asitlere ait ayrı ayrı bileşenlerin konsantrasyonu yüksek hassasiyetle tahmin edilememiştir. UV-vis ve mid-IR verileriyle kemometrik modellerin kullanılması, özellikle üzüm sirkesi için %5'in üzerindeki tağşiş seviyelerini değerlendirirken yüksek oranda doğru sınıflandırma, hassasiyet ve özgüllük elde edilmesini sağlamıştır. Mid-IR'nin performansı, elma sirkesinde beyaz sirke ve ilave asetik asit varlığının tespitinde başarı göstermiştir. Genel olarak, bu tezle, konsantrasyon tahmini ve sirke tağşişinin tespiti için kemometrik araçların önemi gösterilerek spektroskopik yöntemlerin kullanışlılığı vurgulanmıştır.
Sirkede tağşişin tespit edilmesinde hedefsiz analiz yöntemlerinin kullanılması ve proses parametrelerinin tahmin edilmesi
Thesis (Doctoral)--İzmir Institute of Technology, Food Engineering, Izmir, 2023
Includes bibliographical references (leaves. 111)
Text in English; Abstract: Turkish and English
Keywords: Fermented foods; Infrared spectroscopy; Fluorescence spectroscopy; Vibrational spectra; Food Engineering; Fermented foods; Fluorescence spectroscopy; Reverse phase chromatography; Vibration spectroscopy; Multivariate statistical process control